2021
DOI: 10.3390/microorganisms9091999
|View full text |Cite
|
Sign up to set email alerts
|

Re-Emergence and Spread of Haemorrhagic Septicaemia in Germany: The Wolf as a Vector?

Abstract: Since 2010, outbreaks of haemorrhagic septicaemia (HS) caused by Pasteurella (P.) multocida capsular type B (PmB) emerged in Germany. In 2017, we noticed a close spatiotemporal relationship between HS outbreak sites and wolf (Canis lupus) territories. Thus, the main objectives of our study were to investigate the molecular epidemiology of German PmB-HS-isolates and to assess the role of wolves as putative vectors of this pathogen. We collected 83 PmB isolates from HS outbreaks that occurred between 2010 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…From the economic standpoint, it reflects the enormous pressure to minimize losses while raising productive animals and the need to meet the sustained increase in the global demand for animal protein [48]. Other additional motivations that may be stimulating this fact are, increasing demands in terms of food safety [59], high zoonotic risk, emerging epidemiological behavior of the disease, and the urgency to establish control plans adapted to the health realities of each country [12,19].…”
Section: Scientific Trends In Vaccines Against P Multocidamentioning
confidence: 99%
See 1 more Smart Citation
“…From the economic standpoint, it reflects the enormous pressure to minimize losses while raising productive animals and the need to meet the sustained increase in the global demand for animal protein [48]. Other additional motivations that may be stimulating this fact are, increasing demands in terms of food safety [59], high zoonotic risk, emerging epidemiological behavior of the disease, and the urgency to establish control plans adapted to the health realities of each country [12,19].…”
Section: Scientific Trends In Vaccines Against P Multocidamentioning
confidence: 99%
“…Several studies have shown that certain genes contribute to infection success [7] and encode the biosynthesis of key structural and metabolic molecules [8][9][10] required for adhesion, iron acquisition, colonization, immune response evasion, and survival in the host. Other researchers have identified important non-genetic factors involved in their pathogenesis; for instance, this microorganism is normally found in the oropharyngeal cavity [11][12][13], and immunological failures attributable to coinfections, environmental changes, or zootechnical stress are observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…The diseases like HS are associated with huge economic loses in Pakistan and a study conducted in 2007 revealed an estimated loss of USD20 million due to HS related morbidity and mortality of livestock (Farooq et al, 2007). The two serotypes of the bacterium that are most prevalent in Southern and Southeastern Asian and tropical Africa include B:2 and E:2 (Orynbayev et al, 2019;Cuevas et al, 2020;Kutzer et al, 2021). The disease outbreaks in…”
Section: Introductionmentioning
confidence: 99%